ADVANCEMENTS IN MINIMALLY INVASIVE SURGERY: IMPROVING PATIENT OUTCOMES AND REDUCING RECOVERY TIME - Dr. Lucia Müller, MD (Modern American Journals, 2025)
Minimally invasive surgery (MIS) has revolutionized the field of surgery by offering patients faster recovery times, reduced risk of complications, and shorter hospital stays compared to traditional open surgery. The integration of innovative technologies, such as robotic-assisted surgery, laparoscopic techniques, and enhanced imaging tools, has further optimized surgical outcomes. This paper explores the advancements in MIS, emphasizing their role in improving patient outcomes and reducing recovery time. We review recent studies and data on the impact of these innovations on various surgical specialties. The results of this review highlight the significant benefits of MIS, along with the challenges that remain in widespread implementation, including cost, access, and training.
Keywords: Minimally invasive surgery, robotic-assisted surgery, laparoscopic surgery, patient outcomes, recovery time, surgical innovations, healthcare technologies.